STRATEGI KOMUNIKASI TOKOH AGAMA ISLAM DAN HINDU DALAM MENJAGA KERUKUNAN UMAT BERAGAMA (STUDI KASUS DI DESA KARANGMULYO KECAMATAN TEGALSARI KABUPATEN BANYUWANGI) - UMAM, KHOTIBUL; Irfan, Didin Ali (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research aims to find out what communication strategies are used byIslamic and Hindu religious leaders to maintain harmony in KarangmulyoVillage, Tegalsari District, Banyuwangi Regency. Communication strategy is aseries that is prepared and planned according to the objectives, so that it canachieve a goal that has been planned and planned so that it is right on targetand runs safely. Communication can occur between people who havedifferences in education, social status, and even the beliefs they hold. In sociallife there must be a figure who is an elder or is embraced by the community. Areligious figure is a person who is used as a figure in society because he has alot of knowledge about religion and is able to place himself in the midst of apluralist society, then will take on social tasks according to his abilities.Harmony between religious communities will not be realized or run wellwithout the important role of religious figures, where religious figures becomerole models for their congregation because they are considered capable andbecome role models for their congregation because they are considered able tobe role models and are expected to be able to minimize internal and externalconflicts. The research method used in this research is a qualitative researchmethod, namely describing phenomena that exist in the field by means ofobservation, interviews, documentation. The time for this research to be carriedout was in June 2024. From the results of the research, researchers canconclude that the communication strategy of Islamic and Hindu religiousfigures in maintaining harmony in Karangmulyo Tegalsari Banyuwangi villageis to carry out several communication strategy steps consisting of variousreligious and non-religious activities.